Quantifying carbon sources for de novo lipogenesis in wild-type and IRS-1 knockout brown adipocytes - Hyuntae Yoo; Gregory Stephanopoulos; Joanne K. Kelleher (Journal of Lipid Research, 2004)
Studies were conducted to evaluate the flux of various carbon sources to lipogenesis during brown adipocyte differentiation. 13C labeling and isotopomer spectral analysis quantified the contribution of metabolites to de novo lipogenesis in wild-type (WT) and insulin receptor substrate-1 knockout (KO) brown adipocytes. Both glucose (Glc) and glutamine (Gln) provided substantial fractions of the lipogenic acetyl CoA for both WT and KO cells in standard media, together contributing 60%. Adding acetoacetate (AcAc; 10 mM) to the medium resulted in a large flux of AcAc to lipid, representing 70% of the lipogenic acetyl CoA and decreasing the contribution of Glc plus Gln to 30%. For WT cells, the fractional synthesis of new fatty acids during 4 days of differentiation was 80% of the total. Similarly, 80% of the lipidic glycerol was derived from Glc in the medium; Gln was not a precursor for glycerol. When Gln was removed from the medium, the contribution of Glc to fatty acid synthesis doubled, replacing most of the contribution of Gln and maintaining total lipogenesis. Conversely, removal of Glc dramatically decreased lipogenesis.These results indicate that Glc's distinct role in lipid synthesis during differentiation cannot be replaced by other carbon sources, consistent with the role of Glc supplying NADPH and/or glycerol for triglyceride synthesis.